Trade-off between robustness, and quality based on dual intermediate significant bits - N. Mohammed, Ghassan; Yasin, Azman; Zeki, Akram M. (2013)
For any digital watermarking system many requirements should be available. The most important requirements are imperceptibility (quality), and robustness. Many studies have tried to enhance these requirements by using different techniques and methods. In this study, a trade-off between the two requirements to find the optimal value based on the existing Dual Intermediate Significant Bit (DISB) and makes a balance between them. However, this is done by finding the best robustness with an acceptable image quality, so that any change on the pixel by attacks would minimally affect the selected bit. The results show that the trade-off have been done and make a balance between the image quality and robustness.